Planned Reliability Improvement Calculation of Iraqi Super Grid Applying Fuzzy Logic Method - Lafta, Yesar Noori (Nahrain University College of Engineering Journal, 2013)
Reliability is an essential measure and important component of all power system planning and operation procedures. It is one of the key design factors when designing complex, critical and expensive systems. This paper presents a fuzzy logic approach for reliability improvement planning purposes.Evaluating the reliability of the complex and large planned Iraqi super grid ;as Al- Khairat generating station with its tie set is intended to be compact to that grid; and determination of the given reliability improvement project are the major goals of the paper.Results show that the Iraqi super grid reliability is improved by 9.64%.In the proposed technique, fuzzy set theory is used to include imprecise indices of different components in normal reliability calculations applying a Matlab program and that method can be used as a powerful tool for planning to improve systems reliablity.